Matthew, Paul, and Others: Asian Perspectives on New Testament Themes - Loader, William; Repschinski, Boris; Wong, Eric (innsbruck university press, 2019)
During the year 2013 the Society of New Testament Studies (SNTS) decided to involve itself in the promotion of young scholars in the Asia-Pacific region for a broader international audience. In cooperation with local institutions conferences were organized with great success. The conference held in 2018 at the Chung Yuan Christian University in Taipei, Taiwan, is the first conference to have its contributions published. Young scholars from Asia-Pacific proudly present New Testament research of an Asian perspective in dialogue with more traditional approaches. - Im Jahr 2013 begann die Society for New Testament Studies (SNTS), junge Forscher im Asiatisch-Pazifischen Raum zu ermutigen, ihre Forschungen einer breiteren Öffentlichkeit vorzustellen. In Zusammenarbeit mit lokalen Institutionen wurden seitdem internationale Konferenzen mit großen Erfolg organisiert. Die Konferenz in 2018 an der Chung Yuan Christian University in Taipeh, Taiwan, ist die erste dieser Reihe, deren Diskussionen nun auch einer breiteren Öffentlichkeit in dieser Dokumentation zugänglich gemacht werden. Forscherinnen und Forscher stellen neutestamentliche Forschungen asiatischer Prägung im Dialog mit anderen Traditionen vor.